2017
DOI: 10.2116/analsci.33.1375
|View full text |Cite
|
Sign up to set email alerts
|

Selective Detection of Carcinogenic Aromatic Diamines in Aqueous Solutions Using 4-(N-Chloroformylmethyl-N-methylamino)-7-nitro- 2,1,3-benzoxadiazole (NBD-COCl) by HPLC

Abstract: Reaction conditions for the selective derivatization of three types of aromatic diamines without clean-up in an aqueous solution using 4-(N-chloroformylmethyl-N-methylamino)-7-nitro-2,1,3-benzoxadiazole (NBD-COCl) have been developed for simple, fast, and selective analysis by HPLC. The aromatic amines were derivatized to give di-NBD-CO-aromatic amines at 35 C for 5 min in a buffer solution at pH 5 containing a low acetonitrile concentration (0 -400 ng/mL, n = 5, r >0.998). The retention times of these di-NBD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…[37,38] Therefore, fluorescence responses of the two films to different amines in vapor phase were tested. [37,38] Therefore, fluorescence responses of the two films to different amines in vapor phase were tested.…”
Section: Fluorescent Films and Their Sensing Performancementioning
confidence: 99%
See 1 more Smart Citation
“…[37,38] Therefore, fluorescence responses of the two films to different amines in vapor phase were tested. [37,38] Therefore, fluorescence responses of the two films to different amines in vapor phase were tested.…”
Section: Fluorescent Films and Their Sensing Performancementioning
confidence: 99%
“…It is reported that NBD derivatives are widely used in amine sensing owing to its sensitivity to the presence of the amines. [37,38] Therefore, fluorescence responses of the two films to different amines in vapor phase were tested. As expected, the fluorescence emission of the two films was quenched when the tested amines were pumped, which should be explained by the photoinduced electron transfer (PET) process between NBDCOOH and diethylamine.…”
Section: Fluorescent Films and Their Sensing Performancementioning
confidence: 99%
“…A large number of reagents have been developed for the fluorescence derivatization of various functional groups such as amines, phenols, thiols, aldehydes and carbonyl groups. [1][2][3][4][5][6][7] However, conventional fluorescence derivatization reagents cannot be applied to many important compounds that do not possess such typical functional groups. An important example of such compounds is aryl halides.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatization reactions are commonly used to enhance and separate the analytical signals for LC, CE, TLC, and so on [14][15][16][17][18][19][20][21][22]. Acid chlorides, which are highly reactive derivatization reagents, react with samples for a short time and produce the corresponding derivatives in addition to a chloride salt.…”
Section: Introductionmentioning
confidence: 99%